Strategi Pengelolaan Keuangan Di SMP Negeri 4 Ngadirojo Pacitan - SOEMANTO, Soemanto; , Dr. Suyatmini, M.Si; , Dr. Sabar Narimo, M.M., M.Pd (2015)
The purpose of this research is to investigate: Isn't it characteristic compilation of monetary budget, isn't it characteristic is source of finance, and isn't it characteristic pertanggung of monetary answer [in] SMP N 4 Ngadirojo Pacitan. This Research use research qualitative because this research will isn't it [regarding/ hit] monetary management in SMP N 4 Ngadirojo Pacitan. Desain in this research use ethnography, is explanation process totally concerning complexity life of group. This research take location in SMP N 4 Ngadirojo Pacitan month of nopember 2013 until december 2013. The results of the study shows that the Budget Planning of SMP N 4 Ngadirojo Pacitan was based on the need analysis through school self-evaluation (EDS). Source of funds were obtained from BOS (School Operational Assistance) (Central Government), DAU (General Allocation Fund), and the contribution by the Committee Guardians. The financial statements at SMP N 4 Ngadirojo Pacitan was accountable to the Department of Education, the School Committee and students guardian